Evaluation of the linear measurements by conventional radiographs and indirect digital images in the endodontic treatment Avaliação de medidas lineares por meio de radiografia convencional e digitalizada no tratamento endodôntico - Nicole Kawauchi; Izabel Regina Fischer Rubira Bullen; Luiz Eduardo Montenegro Chinellato (University of São Paulo, 2004)
INTRODUCTION: A successful endodontic therapy depends on the linear measurements obtained by means of radiographs taken during odontometry and also on the application of the established working length up to the final obturation. OBJECTIVE: The aim of this study was to compare the precision of the linear measurement obtained by means of conventional radiographs and indirect digital images evaluated by the Digora 1.5 software during the different stages of endodontic treatment, as well as to evaluate the tools available on this software. METHODS: A total of 160 radiographs of single-rooted teeth were obtained from files, which were analysed and divided in 4 groups comprising odontometry, cone fit, condensation and the final obturation. Analyses of the conventional radiographs and digitized images were performed by five previuosly calibrated examiners. RESULTS: A high level of inter and intra-examiner agreement was observed through application of the Kendall coefficient and the correlation index, respectively. In relation to the results of linear measurement, the two-way variance analyses and the Tukey test revealed that, concerning the method, a statistically significant decrease was observed on the measurement obtained through the digital method when compared to the conventional radiograph (p<0,05). Moreover, the measurement presented a statistically significant difference among the different stages of endodontic treatment. Regarding interpretation of the digitized image, there was a statistically significant preference towards the Brightness and Contrast tool of the Digora 1.5 software, as evaluated through the Friedman test. CONCLUSION: The present study demonstrated that image processing by the digital method aids the radiographic interpretation and consequently the determination of reference points for the achievement of the small linear measurements of endodontic treatment. The digital image provided statistically significant smaller linear measurements than those obtained by the conventional method. A radiologia digital tem sido amplamente difundida na odontologia, especialmente na endodontia. O sucesso do tratamento endodôntico depende das medidas lineares obtidas a partir de radiografias tomadas durante a odontometria, e do seguimento do comprimento de trabalho determinado até a obturação final. Este trabalho objetivou comparar a precisão das medidas lineares obtidas em radiografias convencionais com as imagens digitais indiretas avaliadas pelo programa Digora 1.5, durante as diferentes fases do tratamento endodôntico, bem como avaliar as ferramentas disponíveis neste programa. Foram analisadas 160 radiografias de dentes unirradiculares, dos arquivos da disciplina de Radiologia do departamento de estomatologia, da Faculdade de Odontologia de Bauru - USP, divididos em 4 grupos referentes a odontometria, prova do cone, comprobatória e obturação final. As análises das radiografias convencionais e das imagens digitalizadas foram realizadas por cinco examinadores previamente calibrados. Constatou-se um alto índice de concordância inter e intra-examinadores, respectivamente, por meio do coeficiente de concordância geral de Kendall e pelo índice de correlação. Os resultados relacionados às medidas lineares, submetidos à Análise de Variância a dois critérios e ao teste de Tukey, revelaram: quanto ao método, uma diminuição estatisticamente significante das medidas obtidas pelo método digital em relação à convencional (p < 0,05); e houve diferença estatisticamente significante entre a Fase 1 (odontometria) e a Fase 4 (obturação final) do tratamento endodôntico. Para a interpretação da imagem digitalizada, houve uma preferência estatísticamente significativa pela ferramenta de ajuste de Brilho e Contraste do programa Digora 1.5, analisado pelo teste de Friedman. Os resultados obtidos nesse estudo demonstraram que a imagem digitalizada proporcionou medidas lineares menores do que as realizados pelo método convencional, contudo não está ainda determinado se essa diminuição, corresponderia a uma maior acurácia do sistema, e, portanto, se traria maiores benefícios clínicos.